Reading foods labels - Skok, Stephen; Video Education Australasia ([Bendigo, Vic] : Video Education Australasia, 2001)
Part A analyses the new regulations by Australia New Zealand Food Authority (ANZFA) governing food labels which will come into force from 2003. In Part B a range of food labelling issues are discussed by industry and academic professionals
Executive producer, Neil Barrett ; editor, Simon Wright ; graphics, Reece Sanders
Presenter: Jenny Tudor
DVD format
Keywords: Australia New Zealand Food Authority; Food -- Labeling -- New Zealand; Food -- Labeling -- Australia